3D application of the coupled criterion to crack initiation prediction in epoxy/aluminum specimens under four point bending. (15th June 2018) - Doitrand, Aurélien; Leguillon, Dominique
Abstract: Until now, the coupled stress and energy criterion has mainly been used in 2D applications, but it is possible to extend it to a 3D case. Herein the crack initiation in epoxy/aluminum bimaterial specimens under four point bending is predicted through a 3D numerical application of the coupled criterion. The stress and the energy conditions are computed by means of 3D finite element modeling of both undamaged and cracked specimens. The crack initiates at the epoxy/aluminum interface, meshes of the cracked specimens take into account the crack topology which is determined using the interface normal stress isocontours. By indirect confrontation to experimental tests on aluminum/epoxy bimaterial specimens of different width, the proposed approach allows determining the interface strength and fracture energy. The blind application of the proposed method to a crack initiation in aluminum/epoxy/aluminum specimens of different epoxy layer thickness under four point bending leads to a reasonable agreement with experimental data.